Augmenter le vocabulaire français grâce à associez des phrases et des images pour les élèves de la classe XII de SMA Kesatrian 1 Semarang - Arina Fikri Nabila; Diah Vitri Widayanti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
This study aimed to analyze the effectiveness of associating sentences and images to increase the French vocabulary of XII-grade students of SMA Kesatrian 1 Semarang. The method used in this study was “one group pre-test and post-test”. The respondents who participated in this study were 15 students from Class XII of SMA Kesatrian 1 Semarang. This research data collection technique uses testing methods in the form of pre-tests and post-tests. This study uses content validity and to determine reliability using the product moment correlation formula, before being used for research, this research instrument was tested on 5 students and obtained results of 0.9400 while the table r is 0.878 so we can say that the instrument is valid. The average pre-test score was 55, while the average post-test score was 79.2. Data were analyzed using a t-test. The calculation results show that the number of t > table t = 5.3341 > 1.761, with db 15-1:14 at the significance level ((α = 5% = 0.05)). Therefore, the hypothesis is accepted, which means that combined sentences and images can be used to increase the French vocabulary of XII-grade students of SMA Kesatrian 1 Semarang.